2018
DOI: 10.1037/cpb0000112
|View full text |Cite
|
Sign up to set email alerts
|

Client dropout from business coaching.

Abstract: Research on client dropout in business coaching is scarce even though dropouts can have consequences for clients, coaches, organizations, and the validity of coaching research. In this article, a conceptualization and definition of client dropout are developed and justified. Client dropout is defined as the early termination of coaching by a client before all coaching sessions and goals are reached. This conceptualization has enabled the author to systematically explore this new construct in two consecutive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
(84 reference statements)
0
4
0
4
Order By: Relevance
“…They may be more open to the idea of change when feeling safe (Kretzschmar, 2010), more receptive of the coaches’ actions, and willing to adopt different perspectives. Clients are also less likely to drop out from coaching (Schermuly, 2018 1 ). When clients exchange these resources, coaches can exchange other psychological benefits in return.…”
Section: Working Alliance and Coaching Outcomes For Clientsmentioning
confidence: 99%
See 1 more Smart Citation
“…They may be more open to the idea of change when feeling safe (Kretzschmar, 2010), more receptive of the coaches’ actions, and willing to adopt different perspectives. Clients are also less likely to drop out from coaching (Schermuly, 2018 1 ). When clients exchange these resources, coaches can exchange other psychological benefits in return.…”
Section: Working Alliance and Coaching Outcomes For Clientsmentioning
confidence: 99%
“…Prior research showed that half of clients experience at least one unintended negative effect from coaching, usually several at once (Graßmann and Schermuly, 2016 1 , 2018 1 ; Graßmann et al, 2018b 1 ; Schermuly et al, 2014). Although the literature on the consequences of unintended negative effects for clients is scarce, first empirical evidence suggests that they are related to client dropout from coaching, which is associated with high costs for clients and coaches (Schermuly, 2018 1 ). However, little is available to help coaches deal with these issues (Kilburg, 2002).…”
Section: Working Alliance and Coaching Outcomes For Clientsmentioning
confidence: 99%
“…AI coaching may though prove unhelpful when clients are severely disrupted and prevented from implementing the chosen solution in their daily lives, such as when receiving strong negative feedback from their supervisors or colleagues (Graßmann & Schermuly, 2016; Schermuly, 2018). Under these circumstances, clients tend to drop out of coaching (Schermuly, 2018). Clients would likely do that in AI coaching as well, as previous studies in psychotherapy have revealed it has comparable dropout rates to traditional face-to-face settings (Rost et al, 2017).…”
Section: Capabilities Of Ai Coaching Along the Coaching Process And Rmentioning
confidence: 99%
“…Wenig ist dazu bekannt wie häufig Coachingprozesse tatsächlich abgebrochen und gegebenenfalls in die Psychotherapie vermittelt werden. Coaches, die bereits einen Abbruch erlebt haben, berichten durchschnittlich sechs Coachingprozesse, die im Laufe ihrer Karriere seitens der Klienten abgebrochen wurden (Schermuly 2018). Mit einer Auftretenswahrscheinlichkeit von über zehn Prozent bei herausfordernden Klienten liegt die Häufigkeit damit höher.…”
Section: Coachingabbruch Als Strategieunclassified
“…Mit einer Auftretenswahrscheinlichkeit von über zehn Prozent bei herausfordernden Klienten liegt die Häufigkeit damit höher. Dies könnte darauf hindeuten, dass Coachingabbrüche inbesondere bei herausfordernden Klienten auftreten und passt du dem Befund, dass Coachingabbrüche auch mit negativen Nebenwirkungen assoziiert sind (Schermuly 2018). Weitere Forschungsarbeiten sind notwendig, um zu untersuchen ob die Beendigung eines Coachingprozesses als erfolgreiche oder nicht erfolgreiche Strategie angesehen wird, sowohl von Coaches als auch von Klienten.…”
Section: Coachingabbruch Als Strategieunclassified